Tribological behavior and wear mechanism of modified nano-SiO2 reinforced epoxy composites - TIAN Jin; GAO Li; CAI Bin; QI Ze-hao; TAN Ye-fa (Cailiao gongcheng, 2019)
Nano-SiO2 surface grafted APTES (T-SiO2) was realized by covalent functionalization technology, and functionalized nano-SiO2 modified epoxy resin composite (T-SiO2/EP) was prepared. The surface functional groups and chemical elements of the functionalized nano-SiO2were analyzed and the mechanical and tribological properties of the T-SiO2/EP were tested. The results show that the mechanical and tribological properties of the epoxy resin are effectively improved due to the introduction of functionalized nano-SiO2. When the content of functionalized nano-SiO2 is 2%(mass fraction, same as below), the microhardness and fracture toughness of the composites (2%T-SiO2/EP) can reach the maximum, which are 70.2HD and 1.02MPa·m1/2 respectively, moreover, in dry friction condition, the friction coefficient and the wear loss reach the minimum, which are 0.49mg and 1.7mg respectively. Compared with pure epoxy resin, they are reduced by 31.9% and 34.6%, and compared with 2% unmodified nano-SiO2 reinforced epoxy resin composite, they are reduced by 14% and 10.5%,and the corresponding wear mechanism is analyzed.